1999
DOI: 10.1021/ac9909812
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Dyes on Ancient Chinese Paper Samples Using the Subtracted Shifted Raman Spectroscopy Method

Abstract: The Stein Collection in the British Library contains the Diamond Sutra, the world's oldest, dated, printed document. The paper of the Diamond Sutra and other documents from the Stein collection is believed to be dyed yellow by a natural extract, called huangbo, from the bark of Phellodendron amurense, which contains three major yellow chromophores: berberine, palmatine, and jatrorrhizine. Conservation of these documents requires definite information on the chemical composition of the dyes but no suitable, comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(43 citation statements)
references
References 38 publications
0
43
0
Order By: Relevance
“…Although this assumption holds good for experiments on tissue samples where exposure times are limited by other constraints, this may not always be the case. As has been pointed out by Bell, Bourguignon, and Dennis, 23,37 and O'Grady et al, 38 there are many situations where it is observed that the random but fixed variations in pixel-to-pixel response on the CCD might actually be more dominant than shot noise. This is especially true when high signal levels can be achieved and exposure times can be increased without any significant downside (such as when chemical mixtures and powder samples are tested).…”
Section: Fluorescence Removal Studymentioning
confidence: 93%
“…Although this assumption holds good for experiments on tissue samples where exposure times are limited by other constraints, this may not always be the case. As has been pointed out by Bell, Bourguignon, and Dennis, 23,37 and O'Grady et al, 38 there are many situations where it is observed that the random but fixed variations in pixel-to-pixel response on the CCD might actually be more dominant than shot noise. This is especially true when high signal levels can be achieved and exposure times can be increased without any significant downside (such as when chemical mixtures and powder samples are tested).…”
Section: Fluorescence Removal Studymentioning
confidence: 93%
“…The theoretical laser shift is provided by moving the diffraction grating position. 8 Errors resulting from the approximate approach are further corrected in the reconstruction algorithm. 9…”
Section: Ssrsmentioning
confidence: 99%
“…Chinese manuscripts Bell et al 2000), a c.13th Century Qur'an (Clark & Huxley 1996) knowledge of which will be used to govern conservation treatments (Chaplin et al 2006). …”
Section: Manuscriptsmentioning
confidence: 99%